Sickle Cell Beta-Plus Thalassemia with Subcapsular Hematoma of the Spleen - Dahal, Suyash; Dahal, Sumit; Ghimire, Dipesh K. C.; Ur Rahman, Ebad; Sharma, Eliza (Case Reports in Hematology, 2017)
While splenic complications like hypersplenism, sequestration crisis, and infarction are commonly reported in sickle cell variants like sickle cell beta-plus thalassemia, splenic rupture with hematoma is rare. We present a case of a 32-year-old young male who presented with dull left upper quadrant pain who was found to have multiple subcapsular splenic lacerations and hematoma on abdominal imaging. Hemoglobin electrophoresis confirmed sickle cell beta-plus thalassemia in the patient. There was no history of trauma, and rest of the workup for possible cause of spontaneous rupture of spleen was negative. With the patient refusing splenectomy, he was managed conservatively. Clinicians need to be aware of this rare complication of sickle cell variants.